طلاق کے اسباب و مراحل میں خاندانی کردار: زوجین، والدین اور دیگر افراد کا جائزہ: The Role of Family in the Causes and Stages of Divorce: An Analytical Study of Spouses, Parents, and Other Relatives (Contemporary Journal of Social Science Review, 2025)
Divorce, once considered a last resort in marital conflict, is now becoming increasingly common in many Muslim societies. This research paper explores the familial causes and involvement in the stages of divorce, with a specific focus on the roles played by spouses, their parents, and other family members. Using an analytical and qualitative methodology rooted in Islamic teachings and contemporary societal realities, the study identifies key patterns that contribute to marital breakdown.It examines how communication gaps, lack of emotional understanding, unmet expectations, and misuse of religious principles by spouses can lead to conflict and separation. Additionally, it investigates the influence of parents in encouraging or discouraging divorce, especially in cases where interference becomes toxic or coercive. The paper also highlights the role of extended family members—such as siblings, in-laws, and relatives—who sometimes aggravate conflicts through bias, manipulation, or undue pressure.Drawing from Qur'anic injunctions, Prophetic guidance, and expert sociological insights, the study underscores the importance of patience, counseling, and reconciliation before reaching the decision of divorce. Furthermore, it offers practical recommendations for pre-marital education, family counseling, and community-based mediation mechanisms to prevent unnecessary divorces. Ultimately, this paper aims to provide a comprehensive understanding of how family dynamics influence the divorce process and what steps can be taken within Islamic frameworks to safeguard marital stability.